The effect of organized auditory stimulations on the consciousness level of comatose patients - shiva Bassampour; masomeh Zakerimoghadam; soghrat Faghihzadeh; fatemeh Goudarzi (Tehran University of Medical Sciences, 2008)
Background & Aim: High frequency of traumatic and non-traumatic brain injuries in one hand and improvement of the health care condition to restore patient;aposs life in the other hand has increased the frequency of comatose patients in ICU. These patients often experience physical, cognitive, behavior or sensory defects, and the sensory input reduction in intensive care units expose them to cognition disorders. It seems that using sensory stimulation programs may be effective in preventing from sensory deprivation and facilitating recovery process.Methods & Materials: In this quasi-experimental study, 30 comatose patients who were hospitalized in ICU in Shariati and Sina hospitals were sought to be studied. The subjects were selected randomly using matching that was placed in case and control group. In the intervention group, patients received an auditory stimulation for 2 weeks, 6 days of a week, 2 times a day. The auditory stimulator was a recorded tape (5-10 minutes) of a familiar voice for 30 minutes. The Glasgow Coma Scale (GCS) was used for measuring the level of consciousness (LOC). LOC was measured before and after each intervention 4 times a day. The control group LOC was measured in a similar manner to the case group. At the same time, homodynamic symptoms (blood pressure, pulse rate, and mean arterial pressure) were measured. Non-parametric test was used for analyzing data. The data was analyzed through SPSS V.11.5 computer software.Results: The findings indicated that there was a significant difference in LOC of the intervention group at the first day and after fourteen days of the intervention (P<0.001), but not in the control group (P=0.769). Although 2 groups were similar in LOC of the first day (P=0.605) but there were a significant difference between their LOC at the fourteenth day (P=0.001).Conclusion: The results showed that the auditory stimulations with familiar voice were effective in increasing LOC in the comatose patients. It is suggested that nurses expose comatose patients with auditory stimulations using a recorded tape of familiar voice in ICU.